Economic Complexity as a Driver of Economic Growth in Indonesia: A Multidimensional Analysis of Trade, Technology, and Research - Putri Maulidar; Chairunnisa Yulfianti; Farhan Hadi Prasetyo (Ekonomikalia Journal of Economics, 2025)
This study investigates how economic complexity influences Indonesia’s economic growth through three interrelated dimensions: research, technology, and trade. Using annual time-series data from 2000 to 2021, several econometric techniques including Ordinary Least Squares (OLS), Robust Least Squares (RLS), Fully Modified OLS (FMOLS), Canonical Cointegrating Regression (CCR), Dynamic OLS (DOLS), and Quantile Regression (QR) are applied to capture both short-run and long-run dynamics. The results reveal that the contribution of economic complexity to growth is heterogeneous and stage dependent. Research and trade-based complexities emerge as the primary long-run drivers of growth, enhancing productivity, export diversification, and structural transformation. In contrast, technology-based complexity exerts a negative effect in both the short and long run, reflecting Indonesia’s limited absorptive capacity, skill mismatches, and institutional constraints. Quantile regression results further show that research-based complexity supports growth during low-performance phases, whereas trade-based complexity becomes more influential at higher stages of development. These findings highlight the need for phase-specific development strategies that strengthen research and innovation in early stages, improve technological absorption during industrial transitions, and promote export sophistication and value-chain integration to achieve resilient, knowledge-driven, and sustainable economic growth.